PELAYANAN POS PELAYANAN TERPADU DESA BAKUNGTEMNGGUNGAN KEC. BALONGBENDO KAB. SIDOARJO PROVINSI JAWA TIMUR DI ERA PANDEMI - Novia Dia Kumala; Sukma Asmaning Putri; Efa Rohmatin Febrian; Ananta Prathama (Universitas Halu Oleo, 2021)
This research discusses the impact of posyandu services in the era of the Covid-19 pandemic for the community in Bakung Village, Temanggungan, Kec. Balongbendo. Where the available services are divided into 3 groups, namely, services for toddlers, pregnant women and the elderly. The purpose of this study was to determine the impact of obstruction of posyandu services for the community caused by the Covid-19 pandemic. To obtain complete data, researchers used qualitative research methods with data collection techniques through observation and interviews. The theory used in this research is descriptive qualitative with hypotheses used subjectively to describe general information. The last stage, draw conclusions by looking for the relationship between the information that has been collected. The results of this study are expected to broaden readers' insights about public services, but it is also hoped that this research can be a reference source for further researchers and as an evaluation material for integrated services in order to further improve the service system during this pandemic and in the future